(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
The biggest challenge surrounding application of polymeric membranes for gas separation is their tradeâ€“off between gas permeation and selectivity. Therefore, the use of mixed matrix membranes (MMMs) comprising inorganic materials embedded into a polymer matrix can overcome this issue. In this work, PES flat sheet membrane and MMMs consists of 10 wt.% of rGO/ZIF-8 hybrid nanofillers were fabricated via dry/wet phase inversion process. Dipâ€coating technique was then used to deposit PEBAX selective layer onto the surface of rGO/ZIF-8 PES support. The effects of PEBAX coating solution concentrations (2, 3 and 4 wt.%) on the permselectivity of CO2 and CH4 were investigated. The as-prepared rGO/ZIF-8 nanofillers and MMMs were characterized by fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (SEM) prior to gas separation performance study. Gas permeation testing was carried out at operating pressure of 1, 3 and 5 bar using CO2 and CH4 gasses. It was observed that the prepared PES membranes and rGO/ZIF-8 PES MMMs did not have any selectivity towards the gases although their permeability was high. As the concentration of PEBAX coating solution increased, thicker coating layer was formed. Therefore, the permeability of CO2 rapidly dropped but the CO2/CH4 selectivity increased significantly up to 38.4. Â Results indicated that the use of 2 wt.% of PEBAX was not effective to form homogenous coating layers on PES membrane and to cover any defects on membrane surfaces, thus, possessing low selectivity of CO2/CH4. The high gas separation performances obtained in this work was due to the synergistic effect rGO and ZIF-8 crystals. In the rGO/ZIF-8 MMMs, the dispersibility are enhanced due to the presence of distorted rGO sheets, while the ZIF-8 component ensure the porosity of the nanofillers and permit gas interactions with the metallic sites and functional groups on the organic linker. These sites facilitate the reactive adsorption leading to enhanced CO2 adsorption as compared to CH4.